What Is the Survival Rate of Implants Loaded Immediately with a Branemark Protocol Prosthesis? A Review - Azarias, Josuel Siqueira [UNESP]; Alves Bento, Victor Augusto [UNESP]; De Moraes Melo Neto, Clóvis Lamartine [UNESP]; Adriazola Ique, Manuel Martin [UNESP]; Do Santos, Daniela Micheline [UNESP]; Goiato, Marcelo Coelho [UNESP] (Thieme, 2024)
The aim of this review was to determine the survival rate of implants loaded immediately with a Branemark protocol prosthesis. An electronic search was performed in the PubMed/MEDLINE database from 2006 to February 2024, using a combination of Medical Subject Headings descriptors: completely edentulous and immediate loading. Human clinical articles in English that evaluated the survival rate of implants loaded immediately with a Branemark protocol prosthesis after placement in the bone were included. A total of 546 articles were identified, of which 15 were included in this study. The 15 articles included in the literature showed a high implant survival rate (more than 93%) after immediate loading.
Keywords: dental; immediate implant loading; implant-supported prostheses; prosthesis; restoration; temporary